HOUGA II SEBAGAI PEMARKAH MODALITAS TOUI DALAM KALIMAT BAHASA JEPANG - Savitri, Rizky; Rini, Elizabeth; Ratna, Maharani (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
In writing this thesis, the writer discussed about „ Houga ii as ModalitiesToui In Japanese Sentence‟. The writer took this theme to examine how thestructure and meaning of houga ii. The purpose of this research is to describe thestructure and meaning of houga ii in Japanese sentences.The method that used in this research is “agih” method. “Agih” method isdata analysis method which is using part of the relevant language as thedetermination tool. Primary data that is used in this research is Haruki Murakami'snovel „1Q84‟. Besides, the data came from a song and the internet (Japanese web).Houga ii has a basic structure yori houga ii, which has functions as acomparison between two different things. Houga ii can be used together withadjective, noun, and verb. Verbs that can be used with houga ii is past tense,dictionary form and negative form. Houga ii also has a variation of a questionform, those question words are „dochira‟ and „izure‟. There is also a variety offorms, that is houga yokatta. Houga ii has the basic meanings 'advice‟ or„comparison'. In Indonesian, houga ii has meaning 'sebaiknya‟ or „lebih baik'.Advice meaning can be used to suggest ourselves, interlocutors/listener, or forthe general case. Houga ii can also indicate of a regret and dissatisfaction.